The effects of coaching on individual outcomes: a mediation model by psychological capital - Fontes, A.; Dello Russo, S. (XV Phd Meeting in Psychology Psychology and Well-being, 2019)
Coaching is a developmental intervention implemented in organisations to improve individual attitudes and behaviours. However, few studies have tested these assumptions and looked at explaining the mechanisms involved. We propose psychological capital (PsyCap), a set of positive individual resources, as a possible mediator. We investigated whether coaching is effective in improving PsyCap, whether it positively impacts individual attitudes and performance via PsyCap, and whether its effects maintain over time. We conducted an experiment with 56 employees in a marketing company, who were either assigned to a coaching intervention or a wait-list control group. Measures of interest were collected before the program started (T1), and after the program had lasted 4 months (T2). A follow-up measure for the experimental group was collected after a further four months (T3). ANOVAs showed coaching was associated with increases in PsyCap, job attitudes, and one dimension of job performance. The mediating role of PsyCap was supported for job attitudes. The effects on PsyCap and job attitudes lasted over time, as revealed by withinsubjects repeated measures analyses. This study fills a gap in our knowledge of the explanatory processes of coaching effectiveness by building on solid research design features, including a control group and a longitudinal design.